Protection of Steel Structures with Paint Coatings in the Context of Environmental Pollution - Dohojda, Marek Henryk; Backiel-Brzozowska, Beata; Dohojda, Bożena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents important problems occurring in the operation of large-size steel structures protected by paint coatings. In our atmospheric conditions, corrosion of steel structures cannot be avoided, even with the use of protective coatings. The problem of environmental pollution with corrosion products and exfoliated paint then appears. When designing corrosion protection, durability of protection is assumed based on environmental corrosivity categories, but in practice degradation of paint coatings can occur much faster.
Keywords: steel structures; corrosion; paint coatings; protection of area; environmental pollution; konstrukcje stalowe; korozja; powłoki malarskie; ochrona powierzchni; zanieczyszczenie środowiska